Potret Perkotaan dalam Menghadapi Globalisasi - Cucu Nurhayati (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2006)
The globalization sweeping the world today has influenced the lives of communities in general. The rapid flow of information and the increasing availability of various facilities also contribute to the acceleration of this process. Events in one part of the world are now more easily observed and imitated by people in other parts. Naturally, this phenomenon will impact the lifestyle of communities, ultimately leading to global changes. The link between globalization and urban development can be seen as a reflection of progress at a higher level. Are our communities ready to face global competition, or are we still preoccupied with internal urban issues that are increasingly prevalent today? It is concerning that while other nations are busy preparing for global competition, we seem to be stagnating. What steps should the government take to address this issue? This is an important issue that needs to be discussed, although it may seem cliché and like an old song with no end in sight.